2022
DOI: 10.1007/s00018-021-04084-2
|View full text |Cite
|
Sign up to set email alerts
|

The wide and growing range of lamin B-related diseases: from laminopathies to cancer

Abstract: B-type lamins are fundamental components of the nuclear lamina, a complex structure that acts as a scaffold for organization and function of the nucleus. Lamin B1 and B2, the most represented isoforms, are encoded by LMNB1 and LMNB2 gene, respectively. All B-type lamins are synthesized as precursors and undergo sequential post-translational modifications to generate the mature protein. B-type lamins are involved in a wide range of nuclear functions, including DNA replication and repair, regulation of chromatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 88 publications
1
42
0
Order By: Relevance
“…In contrast, a recent study revealed that lamin B1 overexpression is significantly associated with poor clinical outcomes in clear-cell renal cell carcinoma [27]. This variability in lamin B1 expression and its association with clinical outcomes suggest that it has different contributions to cancer progression that appear to be cancer type specific [29]. Accordingly, there is a need to evaluate lamin B1 expression in different malignancies, especially since it has been proposed as drug target for certain anticancer therapies (for example, the use of botulinic acid for pancreatic cancer treatment) [25].…”
Section: Introductionmentioning
confidence: 88%
“…In contrast, a recent study revealed that lamin B1 overexpression is significantly associated with poor clinical outcomes in clear-cell renal cell carcinoma [27]. This variability in lamin B1 expression and its association with clinical outcomes suggest that it has different contributions to cancer progression that appear to be cancer type specific [29]. Accordingly, there is a need to evaluate lamin B1 expression in different malignancies, especially since it has been proposed as drug target for certain anticancer therapies (for example, the use of botulinic acid for pancreatic cancer treatment) [25].…”
Section: Introductionmentioning
confidence: 88%
“…LMNB1 was thought to help CD14 monocyte trafficking from the endothelial barrier. And XAF1 and DYSF induced the interacted cells damages [46] , [47] , [48] , [49] , [50] , [51] . Notably, the profile of IL-1β signaling and IL-8 was related to KD [52] , [53] ; however, our findings suggest that IL-1β signaling and IL-8 are irresponsible for the share vascular lesions between KD and COV as only a few genes' expression was found to be targeted in KD and FLU and near no positive gene could be identified in COV.…”
Section: Discussionmentioning
confidence: 92%
“…Disruption of chromatin architectural genomic elements or proteins has emerged as a mechanism underlying diseases ranging from developmental defects to laminopathies and certain cancers ( Lupianez et al, 2016 ; Evangelisti et al, 2022 ; Shin and Worman, 2022 ). The discovery of nuclear architectural defects linked to these diseases provides opportunities to test whether modeling would help understand consequences of the diseases on genome integrity, and in the most optimistic scenarios help identify causes of the pathologies.…”
Section: Modeling Chromatin-nl Interactions To Better Understand Dise...mentioning
confidence: 99%